Original paperMapping of dose distribution from IMRT onto MRI-guided high dose rate brachytherapy using deformable image registration for cervical cancer treatments: preliminary study with commercially available software - Kim, Hayeon; Huq, M. Saiful; Houser, Chris; Beriwal, Sushil; Michalski, Dariusz (Journal of Contemporary Brachytherapy, 2014)
Purpose: For patients undergoing external beam radiation therapy (EBRT) and brachytherapy, recommendations for target doses and constraints are based on calculation of the equivalent dose in 2 Gy fractions (EQD2) from each phase. At present, the EBRT dose distribution is assumed to be uniform throughout the pelvis. We performed a preliminary study to determine whether deformable dose distribution mapping from the EBRT onto magnetic resonance (MR) images for the brachytherapy would yield differences in doses for organs at risk (OARs) and high-risk clinical target volume (HR-CTV). Material and methods: Nine cervical cancer patients were treated to a total dose of 45 Gy in 25 fractions using intensity-modulated radiation therapy (IMRT), followed by MRI-based 3D high dose rate (HDR) brachytherapy. Retrospectively, the IMRT planning CT images were fused with the MR image for each fraction of brachytherapy using deformable image registration. The deformed IMRT dose onto MR images were converted to EQD2 and compared to the uniform dose assumption. Results : For all patients, the EQD2 from the EBRT phase was significantly higher with deformable registration than with the conventional uniform dose distribution assumption. The mean EQD2 ± SD for HR-CTV D90 was 45.7 ± 0.7 Gy vs. 44.3 Gy for deformable vs. uniform dose distribution, respectively (p < 0.001). The dose to 2 cc of the bladder, rectum, and sigmoid was 46.4 ± 1.2 Gy, 46.2 ± 1.0 Gy, and 48.0 ± 2.5 Gy, respectively with deformable dose distribution, and was significantly higher than with uniform dose distribution (43.2 Gy for all OAR, p < 0.001). Conclusions : This study reveals that deformed EBRT dose distribution to HR-CTV and OARs in MR images for brachytherapy is technically feasible, and achieves differences compared to a uniform dose distribution. Therefore, the assumption that EBRT contributes the same dose value may need to be carefully investigated further based on deformable image registration.